(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
This paper implements efficient techniques for cloth simulation in the area of cloth model, numerical integration, collision detection and response. The whole procedure combines the accurate bending model with implicit integration and collision response. Collision response remains a serious difficulty in cloth simulation, especially with implicit integration. We propose a general scheme that integrates collision response into implicit models recovering most of the nice draping movements of the cloth. Collision detection between human body and cloth is accelerated by Axis Aligned Bounding Box (AABB). A cloth draped on a human model is tested for the combined techniques we put forward. Experimental results reveal that this procedure is suitable for the accurate cloth simulation which preserves folds and wrinkles. The scheme that combines implicit integration and two-stage collision response is efficient for cloth simulation.